Adverse effects of type 2 diabetes mellitus on ovarian reserve and pregnancy outcomes during the assisted reproductive technology process - Qin, Xue; Du, Junhong; He, Ruifen; Li, Yi; Zhu, Qinying; Li, Yaxi; Li, Hongli; Liang, Xiaolei (Frontiers in Endocrinology, 2023)
Objective: To study the effect of type 2 diabetes mellitus（T2DM）on overall ovarian reserve and pregnancy outcomes during assisted reproductive technology (ART) among childbearing infertile women. Design: Retrospective cohort study. Setting: The Reproductive Medicine Special Hospital, The First Hospital of Lanzhou University, between January 2019 and December 2022. Patient(s): A total of 265 infertile female patients aged 20–45 years who underwent in vitro fertilization-embryo transfer (IVF-ET), intracytoplasmic sperm injection-embryo transfer (ICSI-ET), or rescue intracytoplasmic sperm injection-embryo transfer (RICSI-ET) in the first fresh cycle. Intervention(s): None. Main Outcome Measure(s): Serum Anti-Müllerian Hormone (AMH) levels, clinical pregnancy rate (CPR), live birth rate (LBR), and abortion rate (AR) in the T2DM group and non-T2DM group. Result(s): Patients with T2DM showed statistically decreased levels of AMH compared to the non-T2DM group. During ovarian stimulation, those with T2DM required significantly higher total and initial doses of gonadotropin (GN), although they had fewer retrieved oocytes and worse pregnancy outcomes than the non-T2DM group. Multivariate logistic regression analysis adjusting for confounding factors showed that T2DM alone was an independent risk factor for CPR and LBR (adjusted odds ratio [a OR], 0.458, adjusted 95% confidence interval [CI], 0.235-0.891, P = 0.022; a OR, 0.227, 95% CI, 0.101-0.513, P<0.001; respectively), and the abortion rate in the T2DM group was 3.316 times higher than the non-T2DM group（a OR, 3.316, 95%CI, 1.248-8.811, P = 0.016;) Conclusions: Infertile patients with T2DM have decreased ovarian reserve, and T2DM has a deleterious impact on clinical pregnancy outcomes during the ART process compared with non-T2DM infertile women. Key words: type 2 diabetes mellitus, ovarian reserve, anti-mullerian hormone, embryonic development, assisted reproductive outcomes